To What End? Policy Objectives and US Public Support for Political Warfare - Dov H Levin (22466263) (2025)
Research regarding military interventions suggests that the objective of an intervention (such as whether it is carried out for humanitarian or power-political ends) substantially influences public support. It is unknown, however, whether that holds for political warfare strategies such as electoral interventions. In a series of survey experiments, we evaluate how different objectives affect US audiences’ support for foreign electoral interventions, both overall and in relation to other forms of political warfare, such as sanctions and covert regime change. Humanitarian objectives elicit greater support than those carried out to stave off threats to US leadership or to promote US economic interests. Furthermore, religious identity affects support for interventions undertaken for humanitarian ends, with the congruence between the identity of respondents and victims substantially influencing support. Finally, support for partisan electoral interventions and other forms of political warfare varies in relation to each other and in relation to interventions’ objectives. Other Information Published in: Foreign Policy Analysis License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1093/fpa/oraf008